The built environment and place attachment: Insights from Japanese cities - Jiuling Li; Mohammad Javad Koohsari; Andrew T. Kaczynski; Ryo Tanimoto; Reo Watanabe; Tomoki Nakaya; Yufeng Luo; Jing Zhao; Akitomo Yasunaga; Koichiro Oka; Tomoya Hanibuchi (Preventive Medicine Reports)
Objective: Place attachment plays an important role in individuals' health and well-being. Understanding the associations between urban design attributes and place attachment can inform strategies to promote place attachment. This study aims to examine the associations between walkable built environment metrics and place attachment. Methods: This study used data collected from October to November 2020, involving 25,340 adults across 21 major cities in Japan. Geographic address information was used to measure objective walkability, while perceived walkability and place attachment were assessed using adapted scales. Ordinary least squares regression models were employed to analyse associations. Results: For individual metrics, three objective measures—availability of destinations, population density, and street integration—were positively associated with place attachment. Several perceived measures, including access to shops, daily life facilities, public green spaces, public transports, the presence of paths, crime safety, and aesthetics, also showed positive associations with place attachment. For composite indices, traditional walkability, space syntax walkability, and perceived walkability were positively correlated with place attachment. Conclusions: These findings demonstrate the associations between walkable built environment metrics and place attachment, showing variations in metric types.